2000
DOI: 10.1103/physrevlett.85.5535
|View full text |Cite
|
Sign up to set email alerts
|

Non-Abelian Energy Loss at Finite Opacity

Abstract: A systematic expansion in opacity, L/λ, is used to clarify the non-linear behavior of induced gluon radiation in quark-gluon plasmas. The inclusive differential gluon distribution is calculated up to second order in opacity and compared to the zeroth order (factorization) limit. The opacity expansion makes it possible to take finite kinematic constraints into account that suppress jet quenching in nuclear collisions below RHIC ( √ s = 200 AGeV) energies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
668
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(720 citation statements)
references
References 17 publications
(50 reference statements)
37
668
4
Order By: Relevance
“…Remarkably, a simple mass dependent energy shift, via Eqs. (15,16), was found to modify all direct and virtual diagrams. This result, proven in the appendices A-G made it possible to generalize the GLV zero mass results to the case of heavy quarks to all orders in opacity.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a simple mass dependent energy shift, via Eqs. (15,16), was found to modify all direct and virtual diagrams. This result, proven in the appendices A-G made it possible to generalize the GLV zero mass results to the case of heavy quarks to all orders in opacity.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus surprising that until now a similar physics mechanism has not been considered for open heavy flavor. In this Letter, we investigated the perturbative QCD dynamics of open charm and beauty production and, in the framework of the reaction operator (GLV) approach [30,31,32,33] extended to composite qq systems, derived the mediuminduced dissociation probability for heavy D-and Bmesons traversing dense nuclear matter. We showed that the effective energy loss, which arises from the sequential fragmentation and dissociation of heavy quarks and mesons, is sensitive to the interplay between the formation times of the hadrons and the QGP and the detailed expansion dynamics of hot nuclear matter.…”
Section: Discussionmentioning
confidence: 99%
“…The GLV reaction operator formalism [30,31] was developed for calculating the induced radiative energy loss of hard quarks or gluons when they pass through a dense medium. In this approach, the multi-parton dynamics is described by a series expansion in χ =…”
Section: Collisional Dissociation Of Heavy Mesonsmentioning
confidence: 99%
“…It is apparent (as assumed in [13]) that the c + b spectra are in good agreement with the electron spectra from heavy flavor decays for p t ∼ > 4 GeV. 6 In this simplified framework we capture the trend of the experimental data, with some room for effects due to heavy quark radiative energy loss. However, since the radial expansion of the QGP will lead to shorter life times of the plasma phase, we now turn to more realistic dynamical models.…”
Section: Heavy-ion Collisionsmentioning
confidence: 99%
“…The quenching of light quarks is well understood as an effect of radiative energy loss when propagating through the medium [5,6]. However, in the case of heavy quarks pure radiative energy loss seems not sufficient to explain experimental data (mainly from electron yields) on heavy flavor quenching [7,8,9,10], suggesting surprisingly strong attenuation.…”
Section: Introductionmentioning
confidence: 99%